Reinnervation of the Diaphragm After Bilateral Phrenic Nerve Resection and Immediate Reconstruction Using a Contralateral Phrenic Nerve Autograft. Issue 5 (November 2020) - Brunetti, Beniamino; Morelli Coppola, Marco; Crucitti, Pierfilippo; Spinelli, Francesco; Stilo, Francesco; Longo, Filippo; Cortese, Livio; Tenna, Stefania; Persichetti, Paolo
Abstract : Abstract: A patient affected by a voluminous synovial sarcoma of mediastinum received radical surgery, resulting in injury of both phrenic nerves. Because of the cancer location, reconstruction of the left phrenic nerve was not possible, so to prevent the patient's ventilator dependence, the right phrenic nerve was reconstructed via an autograft from the residual proximal stump of the contralateral one. In 3 months, the right hemidiaphragm function showed a full recovery, documented by ultrasonographic and radiographic assessment of diaphragmatic excursion, and the patient was weaned from mechanical ventilation. When a nerve autograft is indicated, the sural nerve still remains the criterion standard, because of the low morbidity of the donor site and ease of harvesting; however, in particular situations, such as in this unique case, the choice of an orthotopic graft may offer promising results. Abstract : Supplemental digital content is available in the text.